Age related macular degeneration and sun exposure, iris colour, and skin sensitivity to sunlight - Khan, J C (BMJ Group, 2006)
BACKGROUND/AIM: It has been suggested that sun exposure may be a risk factor for age related macular degeneration (AMD) and that skin sensitivity to sunlight and iris colour could be confounding factors. The aim was to investigate this further in the white population. METHODS: 446 cases with end stage AMD were compared with 283 spouse controls. Data on sun exposure, places of residence, iris colour, subjective assessment of change in iris colour, hair colour at age 20, and skin sensitivity were obtained using a questionnaire. Iris colour was graded clinically by comparison with standard photographs. AMD was graded using stereoscopic colour fundus photographs as well as clinical examination and was defined as the presence of geographic atrophy or choroidal neovascularisation. All variables were included in a multiple logistic regression model including age, sex, and smoking. RESULTS: There was no association between AMD and sun exposure or related factors except for the suggestion of an association between sunburn prone skin type and geographic atrophy which reached borderline significance. CONCLUSIONS: No significant association between AMD and sun exposure, iris colour, change in iris colour, or hair colour was demonstrated.